Contribution of domestic and Interbull records to reliabilities of single-step genomic breeding values in dairy cattle - J. Bauer; J. Přibyl; L. Vostrý (Czech Journal of Animal Science, 2015)
The method of approximating reliabilities of genomic breeding values in the single-step genomic BLUP evaluation procedure of Misztal et al. (2013) was used to evaluate the increase in reliability of breeding values for milk production in dairy cattle brought about by the inclusion of genomic data. Three strategies for approximation of reliabilities were compared: using only domestic records from performance testing of cows in the Czech Holstein dairy cattle population, using the same records in combination with Interbull breeding values of sires expressed as deregressed proofs, and using only the Interbull breeding values of sires expressed as deregressed proofs. The highest average reliability of genomic breeding values was achieved by the strategy using both domestic and Interbull data, for which the approximated reliabilities of genotyped bulls increased by 0.063. This general increase in reliability of genomic breeding values was small due to the small number of reference bulls available for the study. The overall increase in reliabilities for the entire population of dairy cattle was low but detectable. That modest increase was partially dependent on the unfavourable ratio of the number of genotyped bulls to the size of the analyzed population. Inclusion of Interbull data dramatically increased the benefits of genotyping in our test case - a relatively small population with substantial genetic contributions of foreign genes.